Du risque "naturel" à la catastrophe urbaine : Katrina - François Mancebo (VertigO)
Any policy is useless if it goes unheeded. Its feasibility is as important as are its objectives. Environment perception is a matter of negotiation and interpretation of facts that has to be part of risk management policies as a condition of their effecticiency. It means that natural risks and natural disasters don't really exist. Hazard acceptability and its integration into urban and land planning is at stake here. Analyzing New-Orleans' recent disaster —hurricane Katrina— we try to give some light on these issues.